Case Report: Bilateral syringocele in an adolescent—area of focus - Osipov, I. B.; Lebedev, D. A.; Uzintseva, A. A.; Sidorova, N. A. (Frontiers in Pediatrics, 2023)
Rationale Cystic dilatation of the bulbourethral gland duct (Cowper's syringocele, CS) is a rare urethral pathology. No more than 150 cases of CS have been reported in the literature, of which the vast majority are children with a unilateral location. Bilateral CS has been reported in eight cases; however, detailed anatomy and clinical manifestations have not been reported. In this study, we report a case of bilateral CS with cavity junctions through the medial septum and its successful minimally invasive treatment in an adolescent. Case presentation A 16-year-old adolescent patient complained of painful urination and post-micturition urinary dribbling. Magnetic resonance imaging (MRI), urethrography, and ureteroscopy data enabled the establishment of the diagnosis and determination of the type of CS. The surgical treatment that was performed was endoscopic marsupialization of both CS chambers. At follow-up examination after 7 months, the complaints had ceased, and there was complete normalization of urination. The maximum flow rate during uroflowmetry was 35 ml per second, on voiding cystourethrography, the residual cavities were not contrasted, and there was no residual urine or bacteriuria. Conclusion MRI and retrograde urethrography made it possible to visualize changes in the bulbous part of the urethra, and ureteroscopy was the leading imaging modality. These studies was applied precisely because of the suspicion of the presence of a cavity communicating with the urethra. Minimally invasive surgical treatment for double-chamber CS was successful with no resulting complications.